Host-size mediated trade-off in a parasitoid Sclerodermus harmandi. - Zhudong Liu; Bingbing Xu; Li Li; Jianghua Sun (PLoS ONE, 2011)
Optimality models of host-parasitoid relationships have traditionally assumed that host quality increases as a function of host size at parasitism. However, trade-offs may play a crucial role in species evolution and should be found in host-parasitoid interactions where the host quality may differ between different sizes. Here, we investigated the effects of host size differences of Monochamus alternatus larva on foraging decisions, parasitism and related fitness in a gregarious ectoparasitoid, Sclerodermus harmandi. Two-choice and non-choice experiments were conducted with M. alternatus larvae to evaluate preference and performance of S. harmandi, respectively. Results from two-choice test showed that adult females prefer to attack large larvae rather than small larvae. In no-choice tests, adult females needed more time to paralyze large larvae than small larvae before laying eggs on the body surface of M. alternatus larvae and had lower survival and parasitism rate on those large larvae. Foraging decisions of S. harmandi led to the selection of the most profitable host size for parasitoid development, which showed more offspring gained on large M. alternatus larvae than on small larvae and got higher body weight on those large hosts. This study demonstrates the existence of trade-off occurring during host-parasitoids interactions according to host size related quality.